Collective Capacity to Aspire? Aspirations and Livelihood Strategies in the Zambezi Region, Namibia - Mascha Aring; Ole Reichardt; Ewaldine Menjono Katjizeu; Brendan Luyanda; Carolin Hulke (The European Journal of Development Research, 2021)
This paper investigates rural development from a micro-level standpoint, focusing on individual and collective aspirations. We aim to deepen understanding of how a person's socio-economic environment shapes their aspirations and simultaneously how aspirations contribute to future-oriented actions. In combining concepts of sustainable livelihoods and aspirations with a context of 'ordinary uncertainties' (Pine, Ordinary uncertainties: remembering the past and imagining the future at times of rupture and mobility. In: Paper presented at the conference "Rurality and Future-Making. Comparative Perspectives from Europe, the Middle East, and the Mediterranean", 22–24 May, Cologne, Germany, 2019), we discuss the role of individual and collective aspirations in developing livelihood strategies. Drawing on qualitative data from field research in Namibia's Zambezi region, we identify crucial factors that influence aspirations: multiple uncertainties, experiences, and role models. Access to diverse experiences and social exchange shapes future-oriented aspirations, and therefore needs to be included in rural development strategies that account for diversity within communities.
Keywords: 330; Namibia; Zambezi region; Aspirations; Livelihoods; Capacity to aspire; Rural development